Assessing Collaborative Governance Outcomes and Indicators across Spatial and Temporal Scales: Stewardship Contract Implementation by the United States Forest Service. Issue 4 (2nd April 2020) - Mattor, Katherine M.; Cheng, Antony S.; Kittler, Brian; McDonough, Maureen
Abstract: Scholarship on collaboration in natural resource management is restricted by a lack of large-N assessments and mixed methods approach to examine relationships between collaborative structures and processes, and management actions and outcomes. This paper examines the relationship between perceived levels of collaboration, collaborative process indicators, and benefits of USDA Forest Service stewardship contracts at a broad spatial and temporal scale using mixed methodology. This study found higher levels of collaboration were strongly associated with jointly initiated processes that included a breadth of interests and utilized a broad range of outreach mechanisms and opportunities for engagement. Highly collaborative processes were closely linked with attaining project objectives and social and economic benefits. Findings contribute to defining collaboration by uncovering the relationship between perceived levels of collaboration, the role of process characteristics, and perceived benefits of collaborative stewardship contracting processes through a large-N dataset ( n  = 1, 064) and case study ( n  = 61) findings.